Characterization of a mesophilic actinobacteria that degrades poly(butylene adipate-co-terephthalate). (November 2020) - Soulenthone, Phouvilay; Tachibana, Yuya; Muroi, Fumihiro; Suzuki, Miwa; Ishii, Nariaki; Ohta, Yukari; Kasuya, Ken-ichi
Highlights: A mesophilicactinobacteria, which degrades poly(butylene adipate- co -terephthalate) (PBAT) was isolated from soil. The isolate grew only in aerobic conditions and degraded PBAT in the temperature range of 20 ˚C to 30 ˚C. BOD biodegradation testing with the strain revealed it could mineralize PBAT to CO2 . Abstract: An aliphatic aromatic copolyester, poly(butylene adipate- co -terephthalate) (PBAT) is a chemically synthetic and biodegradable polymer that exhibits good mechanical properties, similar to those of low-density polyethylene (LDPE), and can be a replacement for LDPE as biodegradable mulch films in the agricultural field. Biodegradability of PBAT is stable at high temperature conditions (50 – 60 ˚C) such as compost environments compared to mild temperature conditions (25 – 37 ˚C) such as soil environments. Considering that PBAT could be used in biodegradable agricultural applications such as mulching film, it is important to investigate the biodegradation mechanism at mild temperatures. In this study, a PBAT-degrading bacterium isolated from a soil environment, designated as strain NKCM 2511, was studied in detail. Genetic and biochemical analysis revealed that the strain belongs to the genus Rhodococcus in the phylum Actinobacteria. The strain grew only in aerobic conditions and formed a clear zone on a PBAT containing plate in the temperature range of 20 ˚C to 30 ˚C. Based on biochemical oxygen demand (BOD) biodegradation testing, among 3 PBAT components, adipicacid and terephthalic acid resulted in low growth rate of the strains (5 % and 7 %, incubated at 25 °C for 20 days), whereas 1, 4-butanediol resulted in good growth of the strains (55 %). The low BOD biodegradation rate of PBAT by this strain (7 %) may be due to such low rates of terephthalic and adipic acid. Additionally, the PBAT degradation rate was proportional to the growth rate in the presence of various carbon sources. Therefore, the strain was an aerobically mesophilic PBAT-degrading bacterium that expressed the PBAT-degrading enzyme constitutively. To our knowledge, this is the first report on a PBAT-degrading actinobacterial strain in mild conditions. This study provides information to better understand the biodegradation mechanism of PBAT under mild conditions such as in fields.